1998
DOI: 10.1007/s004270050186
|View full text |Cite
|
Sign up to set email alerts
|

The ecdysone receptor and ultraspiracle regulate the timing and progression of ovarian morphogenesis during Drosophila metamorphosis

Abstract: Ecdysteroids regulate insect metamorphosis through the edysone receptor complex, a heterodimeric nuclear receptor consisting of the ecdysone receptor (EcR) and its partner ultraspiracle (USP). Differentiation in the Drosophila ovary at metamorphosis correlates with colocalization of USP and the EcR-A isoform in all but one of eight mesoderm-derived somatic cell types. The one exception is the larval terminal filament (TF) cells, in which only USP is detectable during cell differentiation. In cells destined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 37 publications
2
91
0
Order By: Relevance
“…However, the titre data shown here do not support this hypothesis, since at stage 3b, when excised viral DNA first appears, 20E has already decreased and continues to drop, whereas polydnavirus replication is most intense up to stage 6. The level of 20E is highest when the reproductive tract is in a phase of intensive cell proliferation and differentiation, which suggests a role in early ovarian morphogenesis, as has been reported for Drosophila (Audit-Lamour & Busson, 1981;Hodin & Riddiford, 1998). Furthermore, ecdysteroid titres were also highest shortly after pupation in pupae of an ichneumonid ectoparasitoid, which does not harbour polydnaviruses (Gelman et al, 2000).…”
Section: Discussionsupporting
confidence: 57%
“…However, the titre data shown here do not support this hypothesis, since at stage 3b, when excised viral DNA first appears, 20E has already decreased and continues to drop, whereas polydnavirus replication is most intense up to stage 6. The level of 20E is highest when the reproductive tract is in a phase of intensive cell proliferation and differentiation, which suggests a role in early ovarian morphogenesis, as has been reported for Drosophila (Audit-Lamour & Busson, 1981;Hodin & Riddiford, 1998). Furthermore, ecdysteroid titres were also highest shortly after pupation in pupae of an ichneumonid ectoparasitoid, which does not harbour polydnaviruses (Gelman et al, 2000).…”
Section: Discussionsupporting
confidence: 57%
“…This corroborates a previous pulse-chase study that indicated a first wave of proliferation at 68-72 h AEL, in which BrdU-retaining somatic cells contributed ∼50% of all TF cells throughout the larval ovary. A second wave of proliferation during third instar occurred gradually and resulted in labeled TF cells that appeared from the medial to the lateral side of the ovary (SahutBarnola et al, 1996), matching the topology of mature filament appearance (Gancz et al, 2011;Godt and Laski, 1995;Hodin and Riddiford, 1998;Sahut-Barnola et al, 1996.…”
Section: A Working Model For Ovarian Niche Differentiationmentioning
confidence: 99%
“…Ecdysone is another hormonal cue that promotes TF formation (Gancz and Gilboa, 2013a;Gancz et al, 2011;Hodin and Riddiford, 1998;Konig et al, 2011). At early larval stages, ecdysone receptors act as repressors of TF differentiation, whereas in the second part of the third instar they become activators of TF differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The first is Epidermal growth factor (EGF), which coordinates PGC proliferation rates with intermingled cell (IC) numbers in the ovary (Gilboa and Lehmann, 2006). The second is ecdysone, which initiates both somatic niches and PGC differentiation (Gancz et al, 2011;Hodin and Riddiford, 1998).…”
Section: Introductionmentioning
confidence: 99%